Possibility of Egg Shell Powder as Replacement in Soil Stabilization (International Journal of Innovative Research in Engineering & Management, 2022)
This report describes a research of the  qualities of soil stabilised using lime and egg shell powder.  Tests were carried out to evaluate the possibility of egg  shell powder in substituting lime, which can make the  whole stabilisation process more cost-effective and  environmentally benign. The results demonstrate that all of  the treated mixtures outperformed the untreated soil in  terms of strength. Egg shell powder was added to the soil in  amounts of 0.5%, 1%, 1.5%, and 2% by weight.  Replacement of up to 50% of the lime used for stabilisation  was tested. It was discovered that replacing 25% of the lime  with egg shell powder provided higher strength qualities  and may be used in practise.
Keywords: Lime; Soil stabilization; Egg shell; improvement; Geotechnical; replacement